(untitled) (Italian Journal of Public Health, 2011)
Background: According to the World Health Organisation, Chlamydia trachomatis (Ct) is the most common sexually transmitted bacterial agent worldwide. The aim of the present study was to determine the prevalence and risk factors for genital infection with Ct among sexually active women (14-60 years of age), in Turin (northern Italy). Methods: A cross-sectional study was performed between January 2002 and December 2007 among sexually active women in Turin. All women were tested for Ct infection using the Amplified Ct Assay (Gen-Probe) on an endocervical specimen. The prevalence was calculated as the proportion of Ct-positive women out of the total study population. Associations between Ct infection and risk factors (socio-demographic, behavioural, and clinical-gynaecological) were analyzed using the Chi-square test. The level of significance was set at 0.05. Risk factors independently associated with Ct infection were determined using a multivariate logistic regression model. The statistical analyses were performed using SPSS (version 17.0). Results: The study included 25,289 women, of whom 1.8% were found to have Ct infection. The prevalence of Ct infection increased significantly from 1.5% in 2002 to 2.2% in 2007 (χ2 =5.6; p-value <0.05). The prevalence significantly increased by decreasing age (χ2 linear trend 213.7; p-value <0.001) and was significantly higher among non-Italian women compared to Italian women (3.3% vs. 1.6%, p-value <0.001). In the multivariate analysis, Ct infection was significantly associated with an adjusted odds ratio higher than 2 for young age (14-24 years), being non-Italian, having had 2 or more lifetime sexual partners, and having had more than 1 partner in the previous six months. Conclusions: Our results showed an increase in Ct prevalence in Turin between 2002 and 2007. A significant association between Ct infection and young age, multiple sexual partners, and originating from Eastern Europe was observed. To reduce the spread of the infection, women with at least one of the above mentioned risk factors, should be encouraged to undergo a free-of-charge Ct testing.